The scholarly communication office as a perspective of action for university libraries - Silva, Eduardo Graziosi [UNESP]; Guimaraes, Jose Augusto Chaves [UNESP] (Ibersid Network, 2023)
Considering the current challenges faced by universi-ties, such as the duty to be accountable to society, the need for greater scientific visibility, high competitive-ness based on international rankings, and the ad-vancement of Information and Communication Tech-nologies, the figure of the scholarly communication of-fice is analyzed within the scope of the university li-brary. To do so, existing scientific communication mod-els are analyzed to arrive at products and services from a scholarly communication office based on a sample of fifteen existing scholarly communication offices in li-braries of universities considered excellent in four in-ternational university rankings. The results show, at dif-ferent stages of development, activities related to open access, copyright, research data management, author identifiers, research impact, metrics, publication, and repositories. It is concluded that the identification and systematization of initiatives related to support services for scientific communication located in libraries, for the purpose of structuring offices of this nature based on the studied reality, lead us to think about the need for librarian training to include a solid foundation in scien-tific communication (with a strong basis in the sociol-ogy of science), not only from a normative point of view, but also from an effectively investigative experience that allows the librarian to put themselves in the posi-tion of the researcher and thus have clarity on the as-pects that require their support.
Keywords: University libraries; Scholarly communication; Scholarly communication offices